User perception of flood mobile homes as shelter relief center - Abdul Rahim, Asiah; Zen, Ismawi; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Abdullah, Che Zulkhairi; Abd. Samad, Nuramirah (IIUM Press, 2017)
This investigation focuses on the effectiveness of a prototyped design of mobile homes for flood relief centres. The inspiration of developing the prototype is because of the great flood that happened in Malaysia in 2014 has revealed a lack of recognition and safety procedures in handling and locating victims in particularly, persons with disabilities (PwDs) (PwDs) and the elderly. Most of the emergency shelters are identified as not user-friendly and inaccessible. The research gaps identified in this study on existing facilities are they lack in privacy, safety and security. The methods of data collection are retrieval of primary data that are obtained from interviews, observations, video recordings and questionnaires. Secondary data are obtained from literature, reliable government and NGO agencies that have relation in disaster and risk managements. Data is analysed in order to identify the level of user perception, acceptance of users and relevance of mobile homes for shelter relief centres in Malaysia. This study on the design of mobile homes and the design prototype will conclude that the design should be efficient, provide privacy for the users, easily constructed, and easily transported by road, by air, by water and standardised to cater the needs of victims during flood disaster.